2011
DOI: 10.1111/j.1365-2095.2009.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of raw and hydrothermically processed Prosopis juliflora seed meal as supplementary feed for the growth of Labeo rohita fingerlings

Abstract: Hydrothermically processed Prosopis juliflora (PJ) seed meal as a supplementary diet for Labeo rohita is found to be rich in protein (330 g kg−1) having antinutritional factors in permissible limits and containing essential amino acids adequately except lysine, methionine and cysteine. Ten iso‐nitrogenous and iso‐energetic diets with crude, soaked and autoclaved seed meal at 20%, 35% and 50% replacement of fish meal were tested (D1–D9, respectively). The growth of fish (weight gain, specific growth rate, feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
1
17
1
2
Order By: Relevance
“…Tabela 2. Valores médios das variáveis de desempenho zootécnico de juvenis de tilápia do Nilo alimentados com dietas contendo farelo de algaroba em substituição ao milho hidrotérmico reduziu significativamente a concentração de fatores antinutricionais na farinha de sementes de P. juliflora, resultando em crescimento superior de juvenis de rohu Labeo rohita alimentados com a farinha tratada frente à farinha sem tratamento (Bhatt et al, 2011). Em adição, os mesmos autores não observaram efeito do tratamento hidrotérmico sobre a digestibilidade da proteína dietética pelos peixes.…”
Section: Resultsunclassified
“…Tabela 2. Valores médios das variáveis de desempenho zootécnico de juvenis de tilápia do Nilo alimentados com dietas contendo farelo de algaroba em substituição ao milho hidrotérmico reduziu significativamente a concentração de fatores antinutricionais na farinha de sementes de P. juliflora, resultando em crescimento superior de juvenis de rohu Labeo rohita alimentados com a farinha tratada frente à farinha sem tratamento (Bhatt et al, 2011). Em adição, os mesmos autores não observaram efeito do tratamento hidrotérmico sobre a digestibilidade da proteína dietética pelos peixes.…”
Section: Resultsunclassified
“…A possible explanation for this might be that P. juliflora seeds are rich in mesquite gum (galactomannans) (Chaires-Martínez et al 2008). Previous research suggested that galactomannans decrease the availability of nutrients and growth of others species (Hossain et al 2003, Sawal et al 2004, Bhatt et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the causes of the negative relationship between MBM inclusion and fish performance. The presence of phenolic compounds, as observed in sorghum (Pinto, Pezzato, Miranda, Barros, & Furuya, ) and mesquite bean seeds, is also associated with lower performance in fish (Bhatt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many plant‐based ingredients contain anti‐nutritional factors, such as phenols, tannins, phytins, non‐starch polysaccharides and protease inhibitors, which may impair nutrient utilization, growth performance and health (Bhatt, Chovatiya, & Shah, ; NRC, ). Al‐Marzooqi and Wiseman () confirmed the presence of tannins, phytic acid and trypsin inhibitors in mesquite seed pods.…”
Section: Introductionmentioning
confidence: 99%